Two synchronous primary mesenteric neuroendocrine tumors in a patient: a case report - Symeonidou, Elissavet; Fouza, Ariadni; Gkoutziotis, Ioannis; Nikolaidou, Christina; Petras, Panagiotis; Mpallas, Konstantinos (Frontiers in Surgery, 2024)
Primary mesenteric neuroendocrine tumors represent a rare clinical entity, challenging to manage, while a combination of imaging is demanded in order to differentiate it from metastatic disease, and set the diagnosis. If the tumor is resectable, surgery is the fundament of the therapeutic approach. The appearance of a second primary mesenteric tumor suggests an unacquainted scenario. The current article presents a case of a 40-year-old woman, who underwent laparoscopic excision of a mesenteric tumor located close to the left pararenal space. Pathology with immunohistochemistry examination reported neuroendocrine tumor grade 2. No further treatment was necessary. Seven months later, 68-Gallium DOTATATE detected another primary neuroendocrine tumor located at the right retroperitoneal space without other lesions. The second tumor was also resected laparoscopically, and the pathology confirmed the diagnosis of another neuroendocrine tumor G2. The postoperative course was uneventful, and six months later the patient is disease-free. The adequacy of 68-Gallium DOTATATE for the preoperative diagnosis of primary mesenteric tumors, the role of the laparoscopic approach, and the extent of lymph node resection are matters addressed in this article.